Where's the Money? An Investigation into the Whereabouts and Uses of Australian Banknotes. (20th September 2019) - Finlay, Richard; Staib, Andrew; Wakefield, Max
Abstract: The Reserve Bank of Australia is the sole issuer and redeemer of Australian banknotes, but between issuance and destruction there is little information about where banknotes go or what they are used for. We estimate the whereabouts and uses of Australian banknotes, and find that 15–35 per cent are used to facilitate legitimate transactions, 4–7 per cent are used for transactions in the shadow economy, while the remainder are non‐transactional. The vast majority of non‐transactional banknotes are likely to be hoarded, and we estimate that 5–10 per cent of outstanding banknotes are lost or collected.